Antimicrobial activities of Cynodon dactylon (L.) Pers. (Bermuda Grass) from Kota Kinabalu, Sabah - Syahriel Abdullah (2014)
Cynodon dactylon (L.) Pers. is a perennial grass that possesses great medicinal values. It is traditionally used as a rejuvenator, wound healing and was believed to be able to cure many diseases and infections. In this study, the bioactive compounds and the antimicrobial activities of the plant extract from various solvents and fractions were investigated. The antimicrobial study was conducted against some selected foodborne (Bacillus cereus, Bacillus subtilis, and Escherichia coli), skin disease (Klebsiella spp., Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pyogenes and Streptococcus pneumonia) and plant pathogens (Ganoderma boninense) via disc and agar diffusion, micro-broth dilution and Thin Layer Chromatography (TLC) bioautography. Crude extraction showed that ethanolic extraction produced the highest yield, up to 7.065%. Phytochemical studies confirmed C.dactylon contains many bioactive compounds such as alkaloids, anthraquinones, cardiac glycosides, terpenoids and steroids, saponins, phenolic compounds, flavonoids, tannins, carbohydrates and proteins. C. dactylon ethanol and ethyl acetate crude extracts were purified and optimized using Solid Phase Extraction (SPE) for further bioactive screening. Bioactive compounds from plant SPE based extract were further profiled and identified using Reverse Phase-High Performance Liquid Chromatography (RP-HPLC) and Liquid Chromatography-Mass Spectrometry Quadrapole-Time of Flight (LC-MSQToF). The antimicrobial study revealed broad spectrum of activity from the plant ethanol and ethyl acetate crude extracts against bacterial pathogens tested (the lowest MIC value for ethanol crude extract was observed against B. cereus (50mgmL-1), B. subtilis (50mgmL-1) and S. aureus (50mgmL-1) while the lowest MIC value for ethyl acetate crude extract was observed against B. cereus (40mgmL-1) and S. aureus (40mgmL-1)). Both ethanol and ethyl acetate crude extracts were further purified using SPE and subjected for further antimicrobial bioassay. Greater antimicrobial activity was observed from flush fractions of ethanol and ethyl acetate SPE extracts in contrast to the elute fractions (the lowest MIC value for ethanol SPE extract was observed against B. cereus (10mgmL-1), B. subtilis (10mgmL-1) and S. aureus (10mgmL-1) while the lowest MIC value for ethyl acetate SPE extract was observed against B. cereus (15mgmL-1) and S. aureus (15mgmL-1)). Weak antimicrobial activity was observed from TLC-bioautography against A. niger while great antimicrobial activity from elute fraction of ethanol SPE extract was observed against G. boninense (MIC=10 mgmL-1). Due to the great antimicrobial activity from elute and flush fractions of C. dactylon ethanol SPE extract, both fractions was further investigated for their phytochemical profile. LC-MSQToF analysis revealed some of the possible antibacterial (Methenamine, Arg Ser Ser, Gln Arg Arg, 3-O-mycarosylerythronolide B, Triterpenoid, Cardenolide glycoside, Pandaroside, Avermectin B1a monosaccharide, Gambierol, Ginsenoside and Halstoctacosanolide) and antifungal (5-oxo-7-octenoic acid, Neocnidilide, Elemicin, Apiole, Stearidonic acid, 17-hydroxylinolenic acid, Tokoronin, Gingerglycolipid B, Cyclopassifloside VII, Ophiopogonin C and Cyclopassifloside V) compounds. Mode of action study based on fluorometric bioassay quantification, leakage of 260nm-absorbing materials and Scanning Electron Microscope (SEM) revealed the disruption of bacterial membrane cell by the plant bioactive compounds leads to the bacterial cell death in some tested pathogens. Luminometric assessment based on ATP quantification however suggested some bacterial pathogens were dead due to other metabolic factors such as inhibition or interference with proteins synthesis, DNA replication, metabolic pathways etc. C. dactylon possesses great potential in combating both human and plant microbial pathogens and have bright future to be further investigated for supplement, alternative medications, or as a biological control agent in combating crop pathogen.